A autonomia do direito comercial e a (re)codificação do direito comercial brasileiro - Faria, Marina Zava de (2020)
This paper aims to discuss about the (re) codification of Commercial Law aiming at the strengthening of the autonomy of Commercial Law as well as the effectiveness and increasing of its values. Thus, a new Commercial Code is defended as a vital center of Commercial Law aligned with the Federal Constitution and serving as a compass for other special legislations. In this sense, the intention was to discuss the autonomy of commercial law; The study of its origin, evolution, purpose, species and rules was studied to understand its propagation over time and to verify if it still persists satisfactorily today. In addition it was inquired about the disparities, subtleties and segregation between the two branches of the Private Law: the Commercial and the Civil. And it immersed itself in the inquiries of the scenario of encoding, decoding and recoding; the importance of these movements as a centralizing and decentralizing mechanism, their effectiveness for society and the market, as well as their effects on the existence and discrepancy between the General Codes and the sparse laws, to ascertain their degree of importance in guaranteeing legal and autonomy in the Brazilian scenario. Therefore, this research included, through the descriptive and analytical method, the investigation of bibliographic reviews, articles and legal magazines about the history, evolution, validity and characteristics of the principles, institutes and particularities of Commercial Law, as well as impacts. together with the construction of legal arguments. Before the interpretation of the data, it was observed that in the Brazilian scenario there is the continuity of the autonomy of commercial law, even though it is weakened. For this reason, it is shown as an alternative, the intention to (re) unite the proper mechanisms of Commercial Law by means of a new Commercial Code. Therefore, considering this research for four specific moments, it was concluded that the commercial recoding will concentrate the ability to (re) structure and (re) affirm the values, autonomy, principles, sources and mechanisms of this legal field, besides to (re) stimulate a more objective, concrete and tangible market in its losses and gains for the various players